Konseptualisasi Hak-Hak Politik dalam Sejarah Periodesasi Demokrasi - Samidi, Raden; Suharno, Suharno (Universitas Medan Area, 2018)
The lower economic community is a strategic target for political actors to launch political actions and promises that signal interest. To anticipate this, efforts needed to increase an awareness of community politics which is not only limited to political actions and activities, but also includes knowledge about politics that can be started by understanding the nature of political rights correctly and comprehensively. Therefore, the purpose of writing this article is to describe the conceptualization of citizens' political rights traced based on the history of the use of the concept of democracy from various periods of time. The method used to compile this article is library research and data analyzed by inductive analysis models. The results obtained from the writing of this article are the conceptualization of the use of political rights based on the history of the use of democracy which began from the time of Ancient Greece (6th to 3rd century BC) until the 20th century.